PREVENTION AND CONTROL OF NON-COMMUNICABLE DISEASES (NCDs) THROUGH INTEGRATEDDEVELOPMENT POSTS (POSBINDU) ON CAMPUS. - Duma, Krispinus; Bahktiar, Rahmat; Fitriany, Evi; Weraman, Pius; Maria, Ida Leida (South Eastern European Journal of Public Health, 2024)
Non-communicable diseases have been increasingly attacking young people lately, and are slowly killing the productivity of the younger generation. The purpose of this study was to describe the risk factors for non-communicable diseases (RF-NCDs) in the campus community. This type of research was descriptive observational, the population was the campus community with respondents from each faculty. Risk factors for NCDs experienced by the campus community were identified through posbindu activities. Results: Around 4.41-20.59% of the campus community participating in the posbindu activities had NCD symptoms. Behavioral risk factors include lack of vegetable and fruit consumption, lack of physical activity and smoking. ‘Intermediate’ risk factors include waist circumference, BMI, uric acid, random blood sugar and cholesterol. Conclusion, symptoms of RF-NCDs in the campus community of Posbindu participants have hidden RF (heredity and behavior) and ‘intermediate’ RF in the form of waist circumference, BMI, cholesterol and uric acid. Commitment is needed for prevention and control of RF-NCDs as early as possible through Posbindu activities.